Holiday [compact disc] (Legacy : Sony Music Entertainment, 2014)
Earth, Wind & Fire's beloved style brings the heat to those chilly winter months with a collection of seasonal interpretations with some exciting surprises. Among the tracks is December, a spirited update of their hit September.